13 bus seats on each bus and 12 seats on each van
If y = x+2 and x = -3 then we can say that y = -3+2 after replacing the 'x' with -3
From here, we just add -3 and 2 to get -1 which is why y = -3+2 turns into y = -1
So together x = -3 and y = -1
They pair up to form (x,y) = (-3,-1)
(f ° g) (x) means the composition of the two functions in this order f (g (x) )
So, given f(x) = - 9x + 9 and g(x) = √(x + 1), you must do this:
f(g(x)) = - 9 [ g(x) ] + 9 = - 9 [√(x+1) ] + 9 => f(g(24) = - 9 √(24 + 1) + 9 = - 9√25 + 9 =
= -9(5) + 9 = -45 + 9 = - 36
Answer: - 36
Answer:
11
Step-by-step explanation:
Hello There!
X=2
To solve this, we first need to understand that when we see an X in parentheses, we multiply the number before it in this case 4 by X.
The answer is 2 because we multiply 4 by 2 which is the x value so 4*2 is equal to 8 and they we add 9 to it because the sum of 6 and 3 is 9.
Finally, our answer we get is 17 so our X value is 2.
Have A Great Day!